Interaction management in rural innovation processes - Elizabeth Roldán Suárez (Ciencia y Tecnología Agropecuaria, 2018)
Innovation, production and marketing of a product results from the interaction between a variety of actors. Thus, the Hub extension model of the governmental program MasAgro seeks to be a space in which maize farmers, extensionists, suppliers of inputs, government, teaching and research institutions, among others, interact with each other to generate individual and collective well-being through innovation. The objective of this work was to analyze the relational structures within the Hubs. To this effect, direct interviews were applied to 457 actors from 10 agroecological regions that make up the Hubs of the maize system in Mexico. The indicators of density, closeness, transitivity and diversity of relationships were measured in two moments of analysis: baseline and final line, through the methodology of analysis of social networks. A "t" test of related samples revealed that for the first three indicators there is a statistically significant difference between moments analyzed (p <0.05), which indicates that the interaction between the actors has been managed in the Hub, placing it as a space in which local structure has been generated and relational capital has been maintained, bases of social capital necessary for the development of innovation processes in the rural sector. These findings may serve program managers and policy makers as a complementary tool for evaluating intervention strategies in the sector.